HOAKS DAN CARA MENGATASINYA PERSPEKTIF NYÀYA DARÚANA - Hari Harsananda (Sanjiwani: Jurnal Filsafat, 2018)
Information is the important thing in this world. Globalisation make the transaction information is better dan more easy at this era, but this fact have a dark side, that is the hoax also easy to be sharing to another people, we have to fight with that. Nyàya Darúana with Praktyakûa,Anumàóa,Upamàóa and Úabda Pramàna concept can explain to us the method to fight back the hoax, so we can get the truth behind the information we get on the network and the other information source